Rapid Evidence Review: Exploring existing coordination mechanisms or methods used by education researchers and or Ministries of Education in Africa to align EdTech research to national priorities that enable the use of evidence in foundational learning policy and implementation - Ampofo, Rudolph; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 17187878 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1141 ZenodoArchiveConcept: 17187877
Keywords: _comingsoon; _r:AddedByMyEducationEvidence